Valoración de la captación de carbono para la conservación ambiental en el Sector la Pita de la Parroquia Quiroga. - Carlín Cedeño, Dimas Javier (2018)
A study was presented on the valuation of carbon capture for the evironmental conservation of the forest resource at La Pita sector, Quiroga parish, for which an identification was made of the areas with the greatest potential for carbon capture in the sector , visits and observation routes to establish the arboreal zones within the studied area, which allowed to make the georeferencing of the areas with potential, characterizing the species of greater presence determined in the five transepts made, each with an area of 1000 m2 (50m x 20m), with which through the application of Ríos methodology (2012) the carbon capture of the 11 characterized species was estimated, whose diameters were greater than 10 cm, from which DAP and height were obtain. With the levels of carbon capture obtained from La Pita site, a comparative table of results was made, with data from similar research carried out in Ecuador and internationally, in which the REDD + methodology for tropical forests was applied. It was found that the studied area had a low carbon capture value equivalent to 873.4985 Ton / ha, which becomes an economic benefit of $87.3498 considering the payment rate proposed by the international REDD+ organisms and the IPCC which is $ 10 / Ton of carbon, which means that La Pita area can´t enter an environmental conservation program.